Pemahaman Hakim Tentang Talak Bid’i dan Penerapannya di Pengadilan Agama Lumajang - Ahmadi (Asy-Syari’ah : Jurnal Hukum Islam, 2016)
Bid’i divorce is a divorce that is handed down to a wife who is still in menstruationor to a wife who had done sexual affair with her husband when she was not in menstruation. Both of this kinds of divorces are prohibited. Bid’i divorce is happened in some cases. This study is categorized as empirical research which the data compiled is in the form of qualitative descriptive data. Theresearcher got the data from observation, interview and documentation. In brief, the result of this study is the definition of bid’i divorce based on judge comprehension of a religious court in Lumajang that is a divorce or “Talak” handed down by a husband to his wife in which the wife is still in menstruation or not in menstruation but she has done sexual affair within which. The practice of bid’i divorce in religious court of Lumajang has ever happened, however the judge has extended to the couple that divorce is forbidden. Then, because of some consideration those are divorce right is husband’s authority, husband do not live in Lumajang, and both of them have made n agreement and could hold the risk. Finally, the judge gave permission to the husband todivorce his wife.